WhatsApp Tele-Medicine - usage patterns and physicians views on the platform - Edward Barayev; Omri Shental; Dotan Yaari; Elchanan Zloczower; Itai Shemesh; Michael Shapiro; Elon Glassberg; Racheli Magnezi (BMC, 2021)
Abstract Background Telemedicine has become an integral part of health care delivery in recent years. One of the leading applications for this use is WhatsApp - a free smartphone application that allows instant messaging with pictures and videos. This study analyzed the emerging role of WhatsApp on reducing the need for referrals to medical specialists and to compare the views of physicians regarding WhatsApp consultations. Methods A cross-sectional study based on an anonymous web-survey was conducted among PCPs and medical specialists working in the Israel Defense Forces Medical-Corps during September and October, 2019. Results Of 201 participants, 153 were PCPs and 48 were medical specialists. 86.9 % of PCPs and 86.5 % of specialists used WhatsApp every day in professional settings. Added workload, potential breaching of patient confidentiality and lack of full documentation of consultations were the main concerns among physicians using the application. 60.7 % of PCPs and 95.7 % of specialists stated that these consultations have reduced the need for in-person appointments at least once a week. Conclusions In times of COVID-19 that require social distancing, WhatsApp provides a simple, readily available platform for consultations between healthcare providers, even to the extent of rendering some in-person appointments unnecessary. Healthcare organizations should address the matters troubling healthcare providers, mainly patient confidentiality and lack of documentation in patients' medical records, while providing adequate compensation for those providing the service during and after work hours.